Inspiration of deceptive rhetoric The Arab Spring is a model - سليمان بثينة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research identifies the origins of the problem of rhetorical deception since ancient times in Plato’s "Georgias", called "Against Rhetoric" or "Against the Statement", which he included as a critique of the orators of ancient Athens, who used linguistic tricks to deceive the masses in a trance and stylistic way. The research will choose the "Arab Spring" model; That misleading media slogan that spread through the horizons of Arab and Western media a decade ago, to be the subject of an approach and analysis.